Uncontrolled burning of solid waste by households in Mexico is a significant contributor to climate change in the country. - Reyna-Bensusan,N; Wilson,DC; Smith,SR (Environmental Research, 2018)
Uncontrolled burning of municipal solid waste (MSW) is an important source of air pollution and is wide spread in many developing countries, but only limited data quantify the extent of domestic open burning of household waste. Here, we present some of the first field data to be reported on the uncontrolled domestic burning of waste. A representative community of Mexico (Huejutla de Reyes Municipality) was investigated and household surveys, interviews with waste operators and a waste characterisation analysis were completed to assess the extent of, and factors controlling, the open burning of waste. Waste collection provision to rural communities was very limited and, consequently 92% of households in rural areas reported that they disposed of waste by uncontrolled burning in backyards or unofficial dumps. Overall, 24% of the total MSW generated in the Municipality was disposed by uncontrolled burning. Urban and periurban areas received twice-weekly collections and the rate of uncontrolled burning was considerably smaller compared to rural households, corresponding to approximately 2% of total waste generation. Carbon equivalency calculations showed that burning waste in backyards represented approximately 6% of the total and 8.5% of fuel related CO2Eq emissions by the municipality. Moreover, the equivalent carbon dioxide (CO2Eq) from black carbon (BC) emitted by uncontrolled burning in backyards was over fifteen times larger compared to methane (CH4) potentially released from equivalent amounts of combustible biodegradable waste disposal at the official dumpsite. An assessment of local respiratory health data showed the incidence of disease was higher in rural than in urban areas, when the opposite trend is typically observed in the international literature; given the high rate of burning activity found in rural areas we suggest that open burning of waste could be a major reason for the apparent poorer respiratory health status of the rural population and requires